Hepatic Metabolomics Profiling of Cyprinus Carpio after Acute Cypermethrin Toxicity - Habotta Ola; Abouelmagd Mamdouh; Halawa Amal; Uno Seiichi (Journal of Veterinary Healthcare, 2018)
In the current study, The GC-MS metabolomics approach was used to evaluate the effect of cypermethrin on the metabolic profile in liver tissue of common carp fish. Fish were exposed to low and high concentrations of cypermethrin (0.1 and 1 µg/L respectively) for 24 and 96 h with subsequent PCA analysis to illustrate the response of the metabolic system after exposure to the pyrethroid. Cypermethrin induced obvious alteration in the intermediates of TCA cycle and encouraged consumption of non-carbohydrate sources in liver at all-time points. Additionally, cypermethrin exposure reduced the level of several amino acids and induced damage to the nucleotides reflecting the effect of cypermethrin on purine metabolism. GC-MS based metabolomics approach is a new and powerful tool to understand the toxicological effects and the underlying mechanism of cypermethrin on fish.
Keywords: Amino acids